The effects of technology anxiety and brand trust on the relationship between brand management's elements and brand loyalty: Malaysian car consumer's perspective
Despite the common perception and various researches in the area of brand management-brand loyalty, findings on the relationship between these variables are rather conflicting. Links between brand management’s elements (product quality, service quality, brand value and brand image) and brand loyalty which is moderated and mediated by technology anxiety and brand trust are not comprehensively understandable. Therefore, there is a need to investigate ways in which brand loyalty can be empirically measured in order for researchers to effectively analyse the key variables related to it. The current study attempted to bridge this existing gap by developing an effective brand loyalty measurement and model. Grasped within the foundation of marketing and brand management literature, this investigation developed a conceptual model that explains the relationships between brand management’s elements and brand loyalty. A meta-analysis technique was employed in this investigation to statistically identify the magnitude and the direction of relationships in a single model based on literature reviewed. The investigation employed such theories (Kano model, Technology Acceptance Model 2, Car Technology Acceptance Model and Choice theory) to measure the interrelationship between brand mangement’s elements and brand loyalty. The objectives of the investigation are: 1) to evaluate the direct effects of brand management’s elements on brand loyalty; 2) to investigate the direct effects of brand management’s element on brand loyalty moderated by technology anxiety; 3) to investigate the indirect effects of brand management’s elements on brand loyalty mediated by brand trust. Based on the proposed model, twelve hypotheses were developed with seven latent variables. Conducting a survey and a pilot test, the measurements were refined and the questionnaire used for the main study was developed. Data was analysed using 205 procured surveys. A structural equation modelling approach using partial least squares (PLS) method was employed to evaluate the measurements and the structural model and to test the research hypotheses and relationships among the latent constructs. The results indicated that although the relationships between the research constructs exist, not all relationships were significantly strong. Brand management’s elements were found to directly influence brand loyalty and technology anxiety was found to moderate the link between product quality and brand image with brand loyalty. The results also indicated the critical mediating effect of brand trust between brand management’s elements and brand loyalty. The investigation compared the meta-analysis results, obtained from independent empirical studies, with the field study results, which were obtained from surveying passenger car consumers. This investigation contributes to academicians and practitioners through the establishment of theoretical, practical and policy development. The investigation addressed the existing gap in the literature, and attempts to resolve the existing mixed views on the studied concepts by examining technology anxiety among car’s consumers. This investigation indicated the need to expand this area of research further by examining the investigated relationship with the influence of other factors to establish brand loyalty in a similar and/or different context of study.